1995
DOI: 10.1055/s-2008-1064536
|View full text |Cite
|
Sign up to set email alerts
|

Surgery of the Internal Nasal Valve

Abstract: Over the past 25 years external rhinoplasty has become increasingly popular. Some rhinosurgeons recommend its use widely, even in routine cases. In our view, however, the classical endonasal approaches remain the first choice. Open rhinoplasty offers an excellent visualization and therefore facility of precise correction, but causes a larger area of wound and scarring. It should, therefore, be restricted to cases of particular difficulties. In the era of minimal invasive surgery, external rhinoplasty advocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Harvesting costal cartilage from the left side may result in tearing of the pleura or pericardium and is therefore contraindicated by some authors [9]. Other authors prefer the right side because left-sided chest pain during the healing process can be confused with cardiac pain [1,3].…”
Section: Discussionmentioning
confidence: 97%
“…Harvesting costal cartilage from the left side may result in tearing of the pleura or pericardium and is therefore contraindicated by some authors [9]. Other authors prefer the right side because left-sided chest pain during the healing process can be confused with cardiac pain [1,3].…”
Section: Discussionmentioning
confidence: 97%
“…In actual fact, longstanding absence of the nasal septum leads in most cases to a downward slippage of the upper lateral cartilages and, hence, to collapse of the middle nasal vault and the internal nasal valve. 16 The presence of spreader grafts is therefore useful in any case, as their function of establishing balanced relations between the rebuilt septum and the upper lateral cartilages fosters the expansion and restoration of the internal nasal valve. The overall result is considerable functional improvement and elimination of the difficulties in nasal respiration constantly afflicting these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several operations have been developed to address this problem and aim at widening the nasal valve angle and/or preventing it from narrowing during inspiration. 6,[8][9][10][11][12][13][14][15][16][17][18][19] The most widely used of these operations involves placing rectangular cartilage grafts, so called spreader grafts, subperichondrally between the septum and the upper lateral cartilage as described by Sheen in 1984 20 (Figure 2). Although originally conceived to bridge the long middle vault in patients with short nasal bones, he soon found that the main advantage of spreader grafts lay in their ability to correct the lack of dorsal support to the lateral walls.…”
Section: Discussionmentioning
confidence: 99%